Minimum-Support Solutions for Radiotherapy Planning - Billups, Stephen C.; Kennedy, Janine M. (Annals of operations research, 2003)
Computer-generated plans for radiation treatment sometimes involve an unnecessarily large number of gantry angles. Such plans are time consuming and expensive to administer because each distinct angle causes a delay while the gantry is repositioned. To address this issue, we consider an optimization model that generates minimum-support solutions to the treatment planning problem - that is, solutions involving a minimum number of gantry angles. This model is a polyhedral concave program, which is solved using a successive linearization algorithm based on work by Mangasarian. [PUBLICATION ABSTRACT]